Optimization of glycerol-based medium composition for antifungal metabolites production by Bacillus subtilis - Zorana Rončević; Ida Zahović; Jovana Grahovac; Aleksandar Jokić; Siniša Dodić; Ivana Mitrović; Jelena Dodić (Universidade de São Paulo, 2022)
Abstract Bacillus species are promising producers of various compounds that have pronounced antimicrobial, antiviral and antitumor activities. Due to its GRAS status, Bacillus subtilis represents an excellent candidate for the usage in plant pathogens biocontrol. In this research, evaluation of antifungal metabolites biosynthesis by Bacillus subtilis ATCC 6633 and optimization of glycerol-based medium composition, using response surface methodology, for the production of compounds effective against Neurospora crassa were investigated. The results of disc-diffusion method indicate that applied Bacillus strain produces compounds with antifungal activity against tested fungus. In order to find optimal cultivation medium composition, the experiments were carried out in accordance with Box-Behnken design, and optimization was performed using the concept of desirability function combined with previously defined mathematical equation, which describes examined bioprocess. The optimization model predicts that maximum inhibition zone diameter against Neurospora crassa of 32.24 mm is achieved when initial content of glycerol, NaNO2 and K2HPO4 were 49.68 g/L, 2.90 g/L and 6.49 g/L, respectively. Additionally, the second optimization set was made to minimize the consumption of medium components and costs of medium preparation. The obtained results are the basis for further research aimed to develop medium appropriate for economically justified production of bioactive compounds at industrial scale.